DAMAGE ASSESSMENT OF HISTORIC EARTHEN SITES AFTER THE 2007 EARTHQUAKE IN PERU - Cancino, Claudia; Farneth, Stephen; Vargas-Neumann, Julio; Garnier, Philippe; Webster, Frederick (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The Pisco earthquake of August 15, 2007 resulted in 519 deaths and 1366 injured, with a total of 650,000 people affected and 80,000 dwellings damaged. Preliminary reports indicated that significant earthen sites were damaged. A few months after the earthquake a rapid assessment to better understand the failure of the affected sites was performed by a multidisciplinary team convened by the Getty Conservation Institute (GCI) in response to a request from the Instituto Nacional de Cultura del Perú (INC). Post-earthquake assessments offer an opportunity to understand why buildings fail and provide information that can serve as the basis for the improvement of seismic performance. Lessons learned from earthquakes and other natural disasters are used to advance construction techniques. More recently, such lessons have fostered the development of the engineering and historic preservation disciplines, as well as the testing and review of current building codes and disaster management policies. The main objective of the GCI rapid assessment was to evaluate the damaged sites while recording pre-existing conditions (abandonment, deterioration or structural interventions) that might have affected their seismic performance. This paper presents the highlights of that evaluation and its implications for the future design and retrofit of earthen buildings.